Aging Microglia and Their Impact in the Nervous System - Eugenin-Leon, J (2024)
Aging is the greatest risk factor for neurodegenerative diseases. Microglia are the resident immune cells in the central nervous system (CNS), playing key roles in its normal functioning, and as mediators for age-dependent changes of the CNS, condition at which they generate a hostile environment for neurons. Transforming Growth Factor β1 (TGFβ1) is a regulatory cytokine involved in immuneregulation and neuroprotection, affecting glial cell inflammatory activation, neuronal survival, and function. TGFβ1 signaling undergoes age-dependent changes affecting the regulation of microglial cells and can contribute to the pathophysiology of neurodegenerative diseases. This chapter focuses on assessing the role of age-related changes on the regulation of microglial cells and their impact on neuroinflammation and neuronal function, for understanding age-dependent changes of the nervous system. © 2024. The Author(s), under exclusive license to Springer Nature Switzerland AG.